Chinese immigrants, journalistic censorship and Mark Twain’s critical humanistic writings - Jiazhao Lin (Humanities & Social Sciences Communications)
Abstract This article examines the impact of journalistic censorship and the ensuing experience of “shame” on the development of Mark Twain’s critical humanistic writings, with particular emphasis on the Morning Call censorship episode. This analytical approach draws upon foundational theories developed by modern critical humanists, particularly Sartre’s existentialist reconceptualization of human agency, Foucault’s archeology of power systems, bell hooks’ concept of “oppositional gaze” and insights from contemporary critical racial theory regarding racial supremacy. The aim is to elucidate the conditions under which an exclusive self identity or a subject of power might engage in critical introspection of its own identity, thereby revealing how individuals maintain agency within de-individualized and institutionalized power structures. This article argues that the internalized gaze, instantiated through the mechanism of censorship, operates as a potentiate of power that engenders a profound sense of “shame” which serves as a critical juncture for Twain, prompting a thorough reassessment of the dialectical interplay between the self and the other. Twain’s meditations on the deleterious impacts of othering practices and exclusionary ideologies within humanistic discourse have given rise to a recurring motif of the “oppositional gaze” in his literary oeuvre, as particularly evidenced in Adventures of Huckleberry Finn (1884) and 3000 Years among the Microbes (1905). The case of Twain’s censorship incident and its aftermath demonstrate that the dual nature of power subjects, as both wielders and subjects of power, can enable internal self-criticism and reflection within humanistic and other ideological discourses.